Factors and Strategies Affecting and Improving Financial Performance of Old Age Protection - Lumban Benget Hutajulu; Wita Juwita Ermawati; Alim Setiawan Slamet (International Journal of Social Science and Business, 2023)
The financial performance of the Old Age Security fund held by BPJS Ketenagakerjaan as an institution that is trusted to provide sustainable social security needs to receive great attention nowadays. This research aims to determine factors and strategies affecting and improving financial performance of old age protection in BPJS Ketenagakerjaan. In this study, there are five independent variables such as: Solvability ratio, effectiveness of membership, effectiveness of dues, efficiency ratio, and varian ratio, while dependent variable is growth assets measured by Return on Net Asset Ratio. T-Test was used to find out the difference of financial condition before and during pandemic, the method of multiple linear regression analysis with dummy variable was utilized with using 2019 and 2020 data to determine the factors that influence financial performance, and SWOT analysis used to determine strategies to improve financial performance. The result of this study shows that financial condition is different before and during pandemic, then solvability, effectiveness of membership, and efficiency factors significantly affect the financial performance of old age security program before and during pandemic. The strategies resulted from SWOT factors include: law enforcement, training, education and etc., related to old age financial performance. At the end, this study is expected to help management in BPJS Ketenagakerjaan improve financial performance of old age security program.